Professional Partnerships: Supporting the Preparation of Pre-Service Teachers Through a Tiered Online Mentoring System - Schwartz-Bechet, Barbara; Gogos, Arhonda (International Journal of Advanced Corporate Learning (iJAC), 2011)
The University of Maryland University Collegeâ??s (UMUC) Department of Education developed a program to increase achievement of secondary school students and increase retention of Master of Arts in Teaching Program (MAT) pre-service teacher candidates entitled, â??Professional Partnerships